(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The presented article analyzes the ways of improving professional training and proposes a model for the formation of the professional competence of a modern physical education teacher. We have determined that modern education needs active, creative specialists who will have fundamental education, will possess formed personal qualities and professional culture. We identified the specific qualities that a future specialist in physical culture should possess and highlighted the main indicators of the professional training of modern teachers. The presented article analyzes the ways of improving professional training and proposes a model for the formation of the professional competence of a modern physical education teacher. We have determined that modern education needs active, creative specialists who will have fundamental education, will possess formed personal qualities and professional culture. We identified the specific qualities that a future specialist in physical culture should possess and highlighted the main indicators of the professional training of modern teachers.